Pt/CeO2 and Pt/CeSnOx Catalysts for Low-Temperature CO Oxidation Prepared by Plasma-Arc Technique - Kardash, Tatyana Y.; Derevyannikova, Elizaveta A.; Slavinskaya, Elena M.; Stadnichenko, Andrey I.; Maltsev, Vasiliy A.; Zaikovskii, Alexey V.; Novopashin, Sergey A.; Boronin, Andrei I.; Neyman, Konstantin M. (Frontiers in Chemistry, 2019)
We applied a method of plasma arc synthesis to study effects of modification by tin ions of the fluorite phase of ceria. By sputtering active components (Pt, Ce, Sn) together with carbon from a graphite electrode in a helium ambient we prepared samples of complex highly defective composite PtCeC and PtCeSnC oxide particles stabilized in a matrix of carbon. Subsequent high-temperature annealing of the samples in oxygen removes the carbon matrix and causes the formation of active catalysts Pt/CeOx and Pt/CeSnOx for CO oxidation. In the presence of Sn, X-Ray Diffraction (XRD) and High-Resolution Transmission Electron Microscopy (HRTEM) show formation of a mixed phase CeSnOx and stabilization of more dispersed ceria species. These factors are essential for the observed high activity and thermic stability of the catalyst modified by Sn. X-Ray Photoelectron Spectroscopy (XPS) reveals the presence of both Pt2+ and Pt4+ ions in the catalyst Pt/CeOx, whereas only the state Pt2+ of platinum could be detected in the Sn-modified catalyst Pt/CeSnOx. Insertion of Sn ions into the Pt/CeOx lattice destabilizes/reduces Pt4+ cations in the Pt/CeSnOx catalyst and induces formation of strikingly high concentration (up to 50% at.) of lattice Ce3+ ions. Our DFT calculations corroborate destabilization of Pt4+ ions by incorporation of cationic Sn in Pt/CeOx. The presented results show that modification of the fluorite lattice of ceria by tin induces substantial amount of mobile reactive oxygen partly due to affecting geometric parameters of ceria by tin ions.